Tunable L-band erbium-doped fibre ring laser by means of induced cavity loss using a fibre taper - M. Melo (2003)
In this paper, we present a continuous-wave tunable fibre ring laser operating in the L-band. A bi-directional pumped L-band erbium-doped fibre amplifier provides gain to the loop. Tunability is achieved by bending a single-mode fibre taper using a micrometer drive, controlling in this way the spectral cavity losses. Laser emission is achieved between 1587 and 1606 nm, and low variation of the output laser power is observed over all the tuning range.